21st Century Skills Through STEAM Education: Analysis of School Leaders’ Perspectives (Journal of Asian Development Studies, 2024)
STEAM is an educational approach that strive for developing students’ STEAM skills to meet the demands of the global workforce. This research examined the role of STEAM education in developing 21st century skills, and the factors influencing the integration of STEAM education in the Pakistani education system. It was a descriptive research. A sample of 100 school leaders, 52 male and 48 female, using a simple random method was selected. Researchers made questionnaire based on a five-point Likert scale was used for data collection after confirming its validity and reliability. The instrument's reliability (α =.87) was calculated. The collected data were analyzed it using SPSS (version 26). This study revealed that the majority of the school leaders agreed about developing 21st century skills through STEAM education such as technology and information literacies, problem solving, critical thinking, leadership, social and civic literacy and responsibility. Most of the leaders also agreed regarding the factors influencing the integration of STEAM education in the Pakistani education system, such as lack of resources and infrastructure, ineffective teacher training, traditional teaching methods, cultural barriers, lack of awareness, lack of budget, traditional testing system, limited collaboration with industry, language barriers, and lack of clear guidance in policy and curriculum. Both Male and female leaders were agreed equally regarding 21st century skills and factors influencing integration of STEAM education. This study recommends that Ministry of Education should minimize the aforementioned factors in order to ensure the effective integration of STEAM education in Pakistani education system and in order to develop 21st century skills among students.